2014
DOI: 10.1111/jdv.12435
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the IL‐4 gene promoter ‐590C/T (rs2243250) polymorphism and susceptibility to autoimmune diseases: a meta‐analysis

Abstract: The present study suggests that the IL-4 rs2243250 polymorphism might be associated with genetic susceptibility to autoimmune diseases, including RA and MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…On the other hand, this study reported a negative association of IL‐4 rs2243250 with GD. This finding is in agreement with previous studies in which no association between IL‐4 rs2243250 polymorphism and GD was identified (Chen et al, ; Heward et al, ; Qiu et al, ; Shen et al, ). However, Hunt and co‐workers suggested that the IL‐4 rs2243250 polymorphism has a protective effect against the development of GD in the UK population (Hunt et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, this study reported a negative association of IL‐4 rs2243250 with GD. This finding is in agreement with previous studies in which no association between IL‐4 rs2243250 polymorphism and GD was identified (Chen et al, ; Heward et al, ; Qiu et al, ; Shen et al, ). However, Hunt and co‐workers suggested that the IL‐4 rs2243250 polymorphism has a protective effect against the development of GD in the UK population (Hunt et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…The same year, Gomes et al reported that increased expression of IL‐4 associated with the TT genotype may contribute to immune surveillance during NSCLC development in Caucasian (Gomes et al, ). Besides, many studies showed that rs2243250 were associated with genetic susceptibility to other diseases, such as asthma, rheumatoid arthritis, and multiple sclerosis (Liu, Li, & Liu, ; Qiu et al, ). In our results, we revealed that rs2243267 and rs2227284, two less studied SNPs, were also found to be associated with lung cancer in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In Chinese RA patients, the TT and CT genotype frequencies were reported to be significantly increased compared to controls, while CC genotype frequency was significantly decreased. Accordingly, T allele was suggested to be a risk factor for RA in Chinese patients (9). Logistic regression analyses also showed that carriers of IL4 T allele (rs2243250) had a significantly increased risk for RA (28).…”
Section: Discussionmentioning
confidence: 96%
“…A further study also indicated that the promoter polymorphism may be useful for assessing RA severity, and IL4 -590 TT genotype showed a significant impact on IL-4, which showed a decreased serum level (8). The SNP IL4 -590 T/C has also been associated with an increased risk to develop RA in Chinese and European patients (9). More recently, a meta-analysis of nine studies reported that the promoter polymorphism of IL4 -590 can be used as a genetic marker for evaluating RA susceptibility and severity (10).…”
Section: Introductionmentioning
confidence: 99%